Mesial prefrontal cortical lesions and timidity in rats. II. Reactivity to novel stimuli - Holson, R R; Walker, C (Physiology & behavior, 1986)
An earlier set of experiments suggested that mesial prefrontal cortical (MFC) lesions in rats enhanced timidity. It was uncertain whether this increased timidity was a general phenomenon, or was restricted to fear of bright, open spaces. The experiments reported here measured behavioral reactivity to a variety of stimuli, under situations where light/dark differences were minimized. It was found that MFC rats were slowed in leaving an open field to enter a small box. In the open field, MFC subjects showed signs of enhanced reactivity, but only when the field was novel and the subjects unhandled. When allowed to choose between four alleys containing varying stimuli, brain-damaged rats avoided novel objects and complex stimuli, but spent more time than controls in contact with other rats in the apparatus. In a test of food neophobia, MFC subjects were not neophobic in a familiar test environment, but did avoid the experimenter more than controls. Finally, duration of barbiturate anesthesia was shortened by MFC lesions, but only under conditions of high novelty. It is concluded that MFC lesions produce a timidity which is not restricted to photophobia.